Burnout syndrome in different teaching levels during the covid-19 pandemic in Brazil - Daniela Karine Ramos; Bruna Santana Anastácio; Gleice Assunção da Silva; Leila Urioste Rosso; João Mattar (BMC, 2023)
Abstract Background This article's purpose is to compare burnout syndrome indicators at different levels of teaching in Brazil during the covid-19 pandemic. The comparison also considers the teachers' quality of life and health, working conditions, and digital competence. Methods The hypotheses of this study are that there are statistically significant differences in teachers' burnout rates, quality of life, working conditions, and digital competences depending on the teaching level. A mixed-methods ex-post-facto survey involved 438 Brazilian teachers, with a mean age of 42.93 years (SD = 9.66), 330 females (75%) and 108 males (25%). Data were collected through an online questionnaire. Statistical analysis of variance (ANOVA) tests was performed to compare groups, the Tukey test for paired comparison of the analyzed groups, and the chi-square to verify the association between variables. Results Higher levels of digital competence were associated with lower burnout syndrome scores. Elementary and middle school teachers presented worse quality of life and health indexes. Adapting pedagogical work involved learning but also overwork, exhaustion, and frustration. Conclusions The study concludes that basic education teachers had higher burnout rate scores than higher education teachers during the covid-19 pandemic and that early childhood education should be treated as a separate category. Trial registration Ethics approval was obtained from the University of Santa Catarina (UFSC) Research Ethics Committee (4.432.063, December 7, 2020). Informed consent was obtained from all subjects.